1997
DOI: 10.3109/01050399709048014
|View full text |Cite
|
Sign up to set email alerts
|

Performance in Quiet and in Noise with the Nucleus® Spectra 22 and the Clarion CIS/CA Cochlear Implant Devices

Abstract: The demographic characteristics and functional results from two cochlear implant adult patient groups are reported. The first group of subjects, implanted with the Nucleus Mini 22 Cochlear Implant System utilized the SPEAK coding strategy available in the SPECTRA 22 speech processor. The second group of subjects, implanted with the Clarion Cochlear Implant System used the CIS coding strategy with the exception of one patient utilizing the CA speech coding strategy. Data are available for 130 Nucleus subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…Duration of deafness is a well‐known factor affecting adult CI performance. Prior studies have showed length of deafness to be the greatest single predictor of postoperative speech perception outcome in postlingually deafened adults 30–35 . Although the majority of these studies included age in their multifactorial analysis, they typically included few participants aged 65 and older.…”
Section: Discussionmentioning
confidence: 99%
“…Duration of deafness is a well‐known factor affecting adult CI performance. Prior studies have showed length of deafness to be the greatest single predictor of postoperative speech perception outcome in postlingually deafened adults 30–35 . Although the majority of these studies included age in their multifactorial analysis, they typically included few participants aged 65 and older.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of hearing loss was defined by patient history and objective diagnostics. If no correlation coefficient was presented but ample data was available, 23‐35 information on DoD and speech perception would be extracted, while patients with prelingual onset of deafness before the age of 5, 23,25,26,32 data of sequential implantations 28 and duplicate patient data 30,31 were excluded. Data was also obtained from published figures and graphs 25,30,34 …”
Section: Methodsmentioning
confidence: 99%
“…Palabras Clave: Implantes cocleares, sistema FM, reconocimiento del lenguaje Abreviaturas: CI = implante coclear; ENV = ambiental; FM = frecuencia modulada; HINT = Prueba de audición en ruido; SNR = tasa señal/ruido I ncreased distance from a speaker, reverberation, and the presence of noise in a listening environment can negatively affect the speech recognition abilities of adults and children with hearing loss (Dubno et al, 1984;Erber, 1971;Finitzo-Hieber and Tillman, 1978;Ross and Giolas, 1971). Although cochlear implantation results in significantly improved speech recognition for adults and children with profound hearing loss (Geier et al, 1999;Svirsky and Meyer, 1999;, persons with cochlear implants (CIs) continue to have significant difficulty understanding speech in noisy environments (Battmer et al, 1997;Dorman et al, 1998;Hamzavi et al, 2001;Fetterman and Dominco, 2002).…”
Section: Sumariomentioning
confidence: 99%